Arene‐Inserted Extended Germa[n]pericyclynes: Synthesis, Structure, and Phosphorescence Properties. Issue 42 (12th June 2017) - Tanimoto, Hiroki; Mori, Junta; Ito, Shunichiro; Nishiyama, Yasuhiro; Morimoto, Tsumoru; Tanaka, Kazuo; Chujo, Yoshiki; Kakiuchi, Kiyomi
Abstract: This report describes the synthesis and characterization of arene‐inserted extended (ArEx) germa[ n ]pericyclynes composed of germanium and 1, 4‐diethynylbenzene units. These novel cyclic germanium‐π unit materials were synthesized with diethynylbenzene and germanium dichloride. X‐ray crystallographic analysis revealed their structures, and the planar conformation of ArEx germa[4]pericyclyne along with the regular aromatic rings. UV/Vis absorption spectra and fluorescence emission spectra showed considerably unique and highly improved character compared to previously reported germa[ n ]pericyclynes. Even in the absence of transition metal components, phosphorescence emissions were observed, and the emission lifetimes were dramatically improved. ArEx germa[ n ]pericyclynes showed high photoluminescence quantum yields, whereas low photoluminescence quantum yields were observed for acyclic compounds. Density functional theory calculations show delocalized orbitals between skipped alkyne units through a germanium tether, and an increase in the HOMO energy level, leading to a small HOMO–LUMO energy gap. Abstract : A link to the future : This report describes the syntheses of arene‐inserted type extended (ArEx) germa[ n ]pericyclynes composed of germanium‐1, 4‐diethynylbenzene units, and their characterization. These novel cyclic germanium‐π unit materials were characterized by X‐ray crystallography, UV/Vis spectroscopy, fluorescence, and phosphorescence emission spectroscopy, which showed characteristic optical properties and large emission lifetimes compared to previous derivatives.